An Analysis of Archipelago Religion and Culture Indonesia and Islamization - Dr. Iskandar Sumarsam; Dr. Midiyanto Taufik; Dr. Ahmadin Ismail Fajri (Al-Qanṭara, 2022)
Abstract Countries that practice Islam in addition, this research makes use of normative research despite the fact that the archipelago is becoming increasingly Islamic. Primary data and secondary data are the two kinds of data that are utilised in this study. This study got three key findings based on the results of the analysis of the data gathered in the field. The first of these findings is that the rise of Islamic religion and culture does not erase local culture. The practise of Islamization does not involve the use of violent coercion. The introduction of Islam was accomplished without violence by means of commerce, the arts, marriage, and education. Second, the effort to reconcile religion and culture is a natural thing that has been done for a long time, and there is evidence that supports it, as Wali Songo promoted Islam by adopting community practises. This is something that has been done for a long time. Each of the three major popular cultures in Indonesia incorporates a significant number of Islamic concepts and symbols; as a result, Islam is frequently seen as an essential cultural resource in Indonesian popular culture. In order for urf to be utilised as one of the justifications in the process of implementing sharia law, it must first satisfy the following criteria: Urf is beneficial (both specifically and generally, acts and words), and it is applicable in a wide variety of contexts.